The great deluge : Hurricane Katrina, New Orleans, and the Mississippi Gulf Coast - Brinkley, Douglas (New York : Morrow, 2006)
An account of Hurricane Katrina and the devastation it left in New Orleans and across the Gulf Coast documents the events and repercussions of the tragedy and its aftermath and the ongoing crisis confronting the region.
Ignoring the inevitable; August 27 (Saturday) -- Shouts and whispers; August 27 (Saturday) -- Storm vs. shoreline; August 28 (Sunday) -- The winds come to Louisiana; August 28-29 (Sunday-Monday) -- What was the Mississippi gulf coast; August 29 (Monday) -- The busted levee blues; August 29 (Monday) -- "I've been FEMA-ed"; August 29 (Monday) -- Water rising; August 30 (Tuesday) -- City without answers; August 30 (Tuesday) -- The smell of death; August 31 (Wednesday) -- Blindness; August 31 (Wednesday) -- The intense irrationality of a Thursday; September 1 (Thursday) -- "It's our time now"; September 1 (Thursday) -- The Friday shuffle and Saturday relief; September 2-3 (Friday-Saturday) -- Getaway (or X marks the spot); September 3 (Saturday) and beyond.
Includes bibliographical references and index.
Keywords: Hurricane Katrina, 2005.; Hurricanes -- Louisiana -- New Orleans; Disaster victims -- Louisiana -- New Orleans; Disaster relief -- Louisiana -- New Orleans; Emergency management -- Government policy -- United States